Impact of partial shading on the P-V characteristics and the maximum power of a photovoltaic string - Teo J.C.; Tan R.H.G.; Mok V.H.; Ramachandaramurthy V.K.; Tan C. (MDPI AG, 2023)
Photovoltaic cells; Solar energy; Characteristic curve; Electrical power; Maximum power; Partial shading; Photovoltaic; Photovoltaic systems; Series-connected photovoltaic modules; Solar irradiances; Solar power generation